2012
DOI: 10.1186/1757-1146-5-25
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of peak plantar pressure in people with diabetes‐related peripheral neuropathy: an evaluation of the DH Pressure Relief Shoe™

Abstract: BackgroundOffloading plantar pressure is a key strategy for the prevention or healing of neuropathic plantar ulcers in diabetes. Non-removable walking casts, such as total contact casts, are currently considered the gold-standard for offloading this type of wound. However, alternative methods for offloading that are more cost effective and easier to use are continually being sought. The aim of this study was to evaluate the capacity of the DH Pressure Relief Shoe™ to offload high pressure areas under the neuro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 36 publications
0
38
0
1
Order By: Relevance
“…The p edar®-X system is a reliable, valid measuring system that is widely used in foot pressure research [7,15,16]. The p edar® insoles size was determined according to each individual's shoe size and calibration of the insole sensors was performed before data sampling.…”
Section: Methodsmentioning
confidence: 99%
“…The p edar®-X system is a reliable, valid measuring system that is widely used in foot pressure research [7,15,16]. The p edar® insoles size was determined according to each individual's shoe size and calibration of the insole sensors was performed before data sampling.…”
Section: Methodsmentioning
confidence: 99%
“…Several noncontrolled studies show that 70% to 96% of plantar foot ulcers can be healed in a reasonable time frame (mean 34‐79 d) with ankle‐high removable offloading devices, provided they are used regularly . Multiple cross‐sectional studies also consistently found that a variety of removable ankle‐high offloading devices were more effective in reducing plantar pressure at the forefoot than a variety of footwear interventions (custom‐made, therapeutic, extra‐depth, conventional, or standard footwear) . No studies were found for weight‐bearing activity or adherence.…”
Section: Recommendationsmentioning
confidence: 99%
“…Also, forefoot offloading shoes effectively offload the forefoot and are more effective than accommodative felt and foam dressings worn in a post‐operative sandal or compared with post‐operative shoes alone . A shoe with removable insole plugs can provide significantly more pressure relief than a control shoe or the patients' own shoes . Using an insole with removable plugs and an arch support can provide even further pressure relief when compared with just using insoles with removable plugs or basic flat insoles …”
Section: Structured Education Aimed At Health Care Professionalsmentioning
confidence: 99%